Hilirisasi Riset Kosmetik Herbal: Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Natural Facial Wash Bebas SLS Berbahan Aktif Aloe Vera, Kunyit, dan Rose Oil - Melinda Januarti; Amalia Shafa Istiqomah; Kayla Deeva Shalaisha; Mochamad Fadli Hidayah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Modern commercial facial cleansers heavily rely on synthetic surfactants like Sodium Lauryl Sulfate (SLS), which are proven to cause skin dryness, irritation, and significant aquatic pollution. Utilizing Indonesia's rich biodiversity offers a strategic alternative for sustainable, skin-friendly cosmetics. This community service aims to empower the community by training them to formulate a biodegradable, SLS-free natural facial wash using active botanicals: Aloe vera, curcumin extract, and rose oil combined with niacinamide. The program implemented a combination of hybrid counseling, focus group discussions (FGD), and hands-on laboratory simulation for local communities using the cold process for natural liquid soap bases. The training successfully increased participants' practical competency by 88%. The resulting natural facial wash demonstrated excellent physical stability, a skin-compatible pH range (5.0–5.5), homogeneous consistency, and elegant organoleptic properties with an aromatherapeutic effect. This program bridges the gap between laboratory pharmaceutical research and household economic scale, fostering community-based green entrepreneurship (pharmapreneurship) while actively reducing domestic chemical waste.